Thermal error modelling and compensation for a coordinate measuring machine - Barakat, Nael (My University, 2000)
A methodology for quasi-static error correction by compensation for an intrinsic Coordinate Measuring Machine (CMM) is proposed and tested in this thesis. It consists of three major parts. In the first part includes a systematic approach to machine kinematic modelling. Using this approach results in an analytically based, forward kinematics model of the machine including its errors. In the second part, the model error functions are identified, at the constant thermal state. At a later stage of the research, error functions identification at varying thermal states. The third part of the proposed methodology includes the actual utilization of the model in a compensation strategy to correct for the machine errors. To visualize the effect of the proposed methodology, the performance of the CMM is evaluated using the standard ASME B.89 test before and after compensation for its errors in the constant thermal state. Dramatic improvements are obtained reducing the machine error in measurement by 93%. A modified version of the B.89 standard incorporating the thermal state of the machine is used to test the machine performance at varying thermal states. Improvement of the CMM performance by reducing the volumetric error by 97% is obtained. The research was expanded by applying the proposed methodology to CMM contouring. Regression analysis was proposed for the models. Thermal sensors were used to provide information to update the models. The CMM behavior was tested through simulation in tracking the diagonals of its work volume. Remarkable improvement in the tracking errors reduction is observed. Results obtained show an improvement in the CMM performance to a level close to machine resolution.
Keywords: Mechanical Engineering; Mechanical Engineering